Industry 4.0 smart reconfigurable manufacturing machines. (April 2021) - Morgan, Jeff; Halton, Mark; Qiao, Yuansong; Breslin, John G.
Highlights: Uniquely explores the state-of-the-art in enabling distributed and decentralized machine control and machine intelligence. Offers unique comparatives of enabling IT & OT technology, machine intelligence paradigms, and future state "smart machine" models. Draws objective answers to research questions relating to reconfigurable design, industry adoption, and enabling future state technology. Presents a vision for next-gen Industry 4.0 manufacturing machines, which will exhibit extraordinary Smart Reconfigurable (SR*) capabilities. Abstract: This paper provides a fundamental research review of Reconfigurable Manufacturing Systems (RMS), which uniquely explores the state-of-the-art in distributed and decentralized machine control and machine intelligence. The aim of this review is to draw objective answers to two proposed research questions, relating to: (1) reconfigurable design and industry adoption; and (2) enabling present and future state technology. Key areas reviewed include: (a) RMS – fundamentals, design rational, economic benefits, needs and challenges; (b) Machine Control – modern operational technology, vertical and horizontal system integration, advanced distributed and decentralized control; (c) Machine Intelligence – distributed and decentralized paradigms, technology landscape, smart machine modelling, simulation, and smart reconfigurable synergy. Uniquely, this paper establishes a vision for next-generation Industry 4.0 manufacturing machines, which will exhibit extraordinary Smart and Reconfigurable (SR*) capabilities.